Effective Empiric Antimicrobial Therapy of Bacterial Meningitis and Encephalitis - Diyan Ajeng Rossetyowati; Ika Puspita Sari; Tri Murti Andayani; Titik Nuryastuti (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2021)
Bacterial meningitis-encephalitis (ME) management therapy is critical to appropriately manage clinical outcomes. This study aims to provide recommendations on appropriate empiric antimicrobial to support the healing period and reduce the risk of disease severity. A cross-sectional study, including inpatients without comorbid diagnosed with bacterial ME, was conducted, and records of antimicrobial prescriptions were obtained. Sociodemographic, clinical (diagnostic), and pharmacological (antimicrobial) variables were assessed. Through multivariate analysis, variables associated with the use of antimicrobials for bacterial infections were identified. A total of 45 patients with ME. The patients, who were from surrounding Center Java and Yogyakarta, had a mean age of 11.27 ± 16.93 years and a male predominance of 56.9% (n = 23). The most frequent bacterial infections were caused by: S. haemolyticus and S. epidermidis (25.93%). A total of 100% the patients (n = 45) received a prescription for empiric antibiotics, predominantly 3rd generation cephalosporin e.c ceftriaxone (35.56%) and cefotaxime (13.33%). Empiric antimicrobials are frequently prescribed for the first management of bacterial ME, are considered an inappropriate practice due to a lack of clinical benefits, increased generation of antimicrobial resistance, and risk of adverse reactions due to the use of medications that patients do not require. Drug utilization studies are a great tool for monitoring how antimicrobial is being used and planning interventions to improve their use.